santika, syelvi juni EVALUASI PROGRAM PENDIDIKAN KESETARAAN PAKET C DI SPNF SKB KOTA BENGKULU: EVALUASI PROGRAM PENDIDIKAN KESETARAAN PAKET C DI SPNF SKB KOTA BENGKULU - santika, syelvi juni (Manajer Pendididikan, 2025)
This study aims to evaluate the implementation of the Paket C equivalency education program at the Non-Formal Education Unit (Sanggar Kegiatan Belajar - SKB) in Bengkulu City using the CIPP (Context, Input, Process, Product) evaluation model. The research employs a descriptive qualitative approach with data collection techniques such as interviews, observation, and documentation. The results indicate that, in terms of context, the program is organized to meet the educational needs of the community who do not yet have a high school diploma. Regarding input, it was found that human resources, facilities, and funding are available; however, there are still challenges in utilizing learning technology. The process aspect shows that the program has been carried out in accordance with the guidelines, but student attendance remains a challenge. As for the product, the program has successfully produced graduates who can continue their education to higher levels or enter the workforce. The conclusion of this study emphasizes that, although the Paket C equivalency education program is functioning well, there are several aspects that need improvement to enhance the effectiveness and quality of the program.